Intravascular Fasciitis of the Jugular Vein Mimicking Thrombosis and Sarcoma: A Case Report - Chen, Guo Xin; Chen, Chu Wen; Wen, Xiao Rong; Huang, Bin (Frontiers in Surgery, 2021)
Background: Intravascular fasciitis is a rare disease that is a reactive proliferative lesion of myofibroblasts. There are rare reports that intravascular fasciitis has invaded the jugular vein as seen in this case. Case Presentation: A 41-year-old female presented with right neck dull pain for 20 days. The appearance of the subcutaneous mass was oval, pink hyaline, well-demarcated, and measuring ~5 mm in diameter. Microscopically, the mass was composed of spindle cells arranged in intersecting fascicles. Immunohistochemical stains showed that the spindle cells were positive for smooth muscle actin and negative for S-100, Desmin, MyoD1, and elastin stains. The nuclei of the spindle cells were relatively uniform, and mitotic activity was observed. The overall morphological and immunohistochemical features are consistent with intravascular fasciitis. Conclusion: Due to the rapid growth and vascular invasion, intravascular fasciitis created a high risk of misdiagnosing it as a sarcoma or thrombosis. Reporting this uncommon case, we raise awareness of this non-neoplastic lesion, and careful, light microscopic examination combined with immunohistochemical staining aids in the diagnosis of intravascular fasciitis.